Sanksi Pidana Terhadap Penimbunan Masker Medis dan Hand Sanitizer Pada Masa Pandemi Covid-19 - I Gede Aditya Triyana; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2021)
Regarding the protection of residents in the Covid-19 pandemic, for example, at this time, namely the hoarding of masks and hand sanitizers by business people, anomalies about the scarcity of goods create conditions where the government and all apparatus jointly examine the causes of the Hoarding of goods. Which resulted in the availability of it being scarce and the price soaring high. From the background, conflicts can be formulated, namely: 1. How do the arrangements for the hoarding of goods occur when goods are scarce according to Law no. 7 of 2014 during the Covid-19 pandemic? 2. What is the criminal sanction for the perpetrators of hoarding medical masks and hand sanitizers in Law No. 7 of 2014 during the covid-19 pandemic? Normative legal research is employed in this study. This research explains that the crime of hoarding and multiplying the prices of masks and hand sanitizers is regulated in Law Number 7 of 2014 concerning Trade. The criminal sanctions given are in Article 107 of Law Number 7 of 2014 concerning Trafficking.